2019
DOI: 10.1556/446.15.2019.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interaction between Traits of Different Genotype Maize in Six Fertilizer Level by GGE Biplot Analysis in Hungary

Abstract: Hungary was one of the main countries in the world as regards the yields reached in maize production. The research was conducted to appraise the effect of NPK fertilizer on traits of different hybrid maize (Fao410, Fao340) at the University of Debrecen and our experiment was carried out in Centre for Agricultural Sciences, Institute of Crop Sciences at Látókép in 2018. NPK fertilizer was applied in six different combinations (0-0-0 control, 30-23-27 first dose, 60-46-54 second dose, 90-69-81 third dose, 120-92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…e nitrogen effect on the quantitative and qualitative properties of maize showed that nitrogen increases the production of dry matter, grain yield, and its components. If there is adequate nitrogen in the soil, crops will have vegetative growth, larger leaf area, and significant yield [29,[35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…e nitrogen effect on the quantitative and qualitative properties of maize showed that nitrogen increases the production of dry matter, grain yield, and its components. If there is adequate nitrogen in the soil, crops will have vegetative growth, larger leaf area, and significant yield [29,[35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, fertilizer's positive effect emphasized raising grain yield, the number of kernels in an ear, and kernel value in different corn genotypes. Fertilizer causes proliferation of the leaf number, leaf size and width, and the plant's dry matter [35][36][37][38][39][40][41]. The number of seeds per row had a minimum effect for treatments and low stability in terms of GGE analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of maize and its cultivation potential worldwide and in Iran, this crop's yield sustainability was studied in previous research. Genotype × environment interaction (GEI) is responsible for genotype sustainability characteristics [2][3][4]. One of the usual exacting effects in plant breeding development is to dissect the genotype × environment (GE) interaction correctly.…”
Section: Introductionmentioning
confidence: 99%